(untitled) (Teología, 2021)
The pages of this article are intended to bring the reader closer to the histor- ical and religious figure of Manuel Costa de los Ríos, popularly known as Negro Manuel, the faithful slave of Our Lady of Luján, by analyzing the act of sale in behalf of the Brotherhood of Our Lady of Luján, in December 1674, with the purpose, according to the express will of its legal owners, to perma- nently serve the Sacred Image. This valuable document constitutes the proof that clears any doubt about the historicity of Negro Manuel, since it reliably certifies the sale, induding his name, origin, age and health conditions.